DAGESTAN AND PEOPLES OF THE NORTH CAUCASUS IN THE SYSTEM OF POLITICAL RELATIONS IN THE FIRST THIRD OF THE XVIII CENTURY - Kidirniazov, D S (History, Archeology and Ethnography of the Caucasus, 2015)
The article shows how during the period under consideration the peoples of the region turned out to be in the circle of interests of three great powers – Russia, the Turkish Empire and Iran. Russia was greatly interested in the Caucasus, due both to objective circumstances of that time and the economic policy of the Russian state, that aspired in short time to create national industry and advanced trade. For its part, Turkey also tried not to miss its chance in the region, but making semblance of loyal relations with Iran and Russia it tried to take advantage of the most powerful rulers of the North Caucasus. The author of the article notes that in spite of ambiguity of the events that took place in this area, general trend of political relationships between the peoples and with the Russian state as well not only preserved, but strengthened. All this was due to common interests and long-term cooperative historical perspectives of the North Caucasus, particularly of Dagestan and Russia.